Role of Panchbhautika Taila Nasya in Socio-Behavioral Disorders - Ayurveda Perspective (International Journal of Ayurveda and Pharma Research, 2023)
Socio-behavioural disorders have a profound impact on affected individuals lives and society at large. The conventional treatment for child and adolescent psychiatric disorders often involves psychopharmacology, which may be associated with adverse side effects. Ayurveda, an ancient traditional system of medicine, offers a multidimensional therapeutic strategy to address these disorders. According to the classics, the unstable status of Mana, Indriya and Atma leads to many socio-behavioural disorders. To address this challenge, Ayurveda have given a multidimensional approach including Medhya rasayanas, Panchakarma procedures like Nasya and nonmedical treatment including Achara rasayana (rejuvenation through the right code of conduct) and Satvavajaya chikitsa. Panchbhautika taila nasya is mentioned in Kashyap samhita for increasing the strength of sensory organs This research article explores the efficacy of Ayurvedic Nasya therapy, particularly Panchbhautik Taila Nasya, as a potential intervention to enhance cognitive function and mitigate socio-behavioural abnormalities.